An altered repertoire of T cell receptor V gene expression by rheumatoid synovial fluid T lymphocytes. - Lunardi, C (1992)
The pattern of T cell receptor V gene expression by lymphocytes from rheumatoid synovial fluid and paired peripheral blood samples was compared using a polymerase chain reaction (PCR)-based assay. Eight rheumatoid arthritis (RA) patients who had varying durations of disease (from 2 to 20 years) were studied. In all patients there was evidence of a different pattern of V gene expression between the two compartments. Significantly increased expression of at least one V alpha or V beta gene family by synovial fluid T cells was observed in all the patients studied. Three different V alpha (V alpha 10, 15 and 18) and three V beta (V beta 4, 5 and 13) families were commonly elevated. Sequencing of synovial V beta transcripts demonstrated that the basis of increased expression of selected V gene families in the synovial fluid was due to the presence of dominant clonotypes within those families, which constituted up to 53% of the sequences isolated from one particular synovial V gene family. There were considerable differences in the NDJ sequences found in synovial and peripheral blood T cell receptor (TCR) transcripts of the same V beta gene family. These data suggest that the TCR repertoire in the two compartments differs, and that antigen-driven expansion of particular synovial T cell populations is a component of rheumatoid synovitis, and is present in all stages of the disease.